A Combined Biomarker of Bright CD38 and MYC ≥55% Is Highly Predictive of Double-/Triple-Hit High-Grade B-Cell Lymphoma: Implication on Diagnostic Workup. Issue 3 (3rd May 2022) - Alsuwaidan, Abdullah; Koduru, Prasad; Fuda, Franklin; Manuel Jaso, Jesse; Chen, Mingyi; Rosado, Flavia; Luu, Hung S; Sweed, Nathan; Garcia, Rolando; Doucet, Meggie; Desai, Neil B; Kumar, Kiran A; et al.
Abstract: Objectives: Diagnosis of high-grade B-cell lymphoma with MYC and BCL2 or BCL6 rearrangements (double-/triple-hit lymphoma [DTHL]) appears to mandate fluorescence in situ hybridization (FISH) testing for all large B-cell lymphoma (LBCL). Given the low incidence of DTHL, we aimed to identify flow cytometry (FC) and immunohistochemistry (IHC) features of DTHL that could be used to develop an optimal screening strategy. This combined FC-IHC approach has not yet been studied. Methods: We compared features of 40 cases of DTHL and 39 cases of diffuse LBCL (DLBCL) without MYC rearrangement. Results: Bright CD38 expression (CD38 bright ) by FC, high MYC expression (≥55%), and double-expressor phenotype by IHC were significantly associated with DTHL. The biomarker combining FC and IHC, CD38 bright and/or MYC ≥55%, was superior to FC and IHC markers alone in predicting DTHL. Restricting FISH testing to approximately 25% of LBCL based on CD38 bright and/or MYC ≥55% would detect approximately 95% of DTHL-BCL2 and approximately 75% of DHL-BCL6. Conclusions: Our study demonstrated that the novel biomarker of CD38 bright and/or MYC ≥55% is highly predictive of DTHL. Awareness of the advantages and limitations of this screening strategy would facilitate development of a rational diagnostic workflow to provide high-quality patient care.